ON THE ROLE OF MAST CELLS AT THE RECOVERY REACTION OF LIVER (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
Here is shown correlative relation between mast cells quantity and scar maturation pace at the resection zone of rats and domestic hens liver during two months after partial hepatectomy.